HUBUNGAN INDEKS MASSA TUBUH DAN TEKANAN DARAH - Nurhayati, Nurhayati; Rudiansyah, Mohammad; Pratiwi, Dewi Indah Noviana; Mutaqqien, Fauzan; Bakhriansyah, Mohammad (Homeostasis, 2024)
Abstract: Hemodialysis is a therapy for patients with kidney disease, both acute and chronic, which is used as a substitute for decreased kidney function. Body mass index (BMI) is a simple measuring tool to see the nutritional status of a person, both men and women. Blood pressure is the process when blood is distributed by the heart throughout the body. The research aims to determine whether there is a relationship between body mass index and blood pressure in patients undergoing routine hemodialysis at Ulin Regional Hospital, Banjarmasin. The method in this research is analytical observational with a cross sectional research design with the Pearson test. This study used patient subjects undergoing routine hemodialysis at the hemodialysis installation at Ulin Banjarmasin Regional Hospital in November 2023 using a simple random sampling technique according to the inclusion and exclusion criteria. Primary data was collected by measuring height, weight and blood pressure and secondary data in the form of numbers. Patient medical records obtained from the hemodialysis installation at Ulin Banjarmasin Regional Hospital. This research uses correlative data analysis techniques which begin with a normality test using the Kolmogorov-Smirnov technique because the number of subjects in this research was 50 people with a subject distribution of 65 people. The results of this study obtained a correlation value for body mass index and blood pressure with a value of p = 0.000 and a value of r = 0.06. Keywords: hemodialysis, chronic renal failure, acute renal failure, body mass index, blood pressure. Abstrak: Hemodialisis merupakan terapi untuk pasien penyakit ginjal baik yang akut maupun kronik yang digunakan sebagai pengganti fungsi ginjal yang menurun. Indeks massa tubuh (IMT) ialah alat ukur sederhana untuk melihat status gizi seseorang baik laki-laki maupun perempuan. Tekanan darah merupakan proses ketika darah dialirkan oleh jantung keseluruh  tubuh. Penelitian memiliki tujuan untuk mengetahui apakah ada hubungan antara indeks massa tubuh dan tekanan darah pada pasien yang menjalani hemodialisis rutin di RSUD Ulin Banjarmasin. Metode pada penelitian ini yaitu observasional analitik dengan desain penelitian cross sectional dengan uji pearsone. Penelitian ini menggunakan subjek pasien yang menjalani hemodialisis rutin di instalansi hemodialisis RSUD Ulin Banjarmasin pada November 2023 dengan menggunakan teknik simple random sampling sesuai kriteria inklusi dan eksklusi. Pengambilan data primer dilakukan dengan melakukan pengukuran tinggi badan, berat badan serta tekanan darah dan data sekunder berupa nomor rekam medik pasien yang didapatkan dari instalasi hemodialisis RSUD Ulin Banjarmasin. Penelitian ini menggunakan teknik analisis data korelatif yang diawali dengan uji normalitas dengan teknik kolmogorov- Smirnov dikarenakan jumlah subjek dalam penelitian ini sebanyak 50 orang dengan distribusi subjek sebanyak 65 orang. Hasil penelitian ini didapatkan nilai korelasi indeks massa tubuh dan tekanan darah dengan nilai p = 0,000 dan nilai r = 0,06. Kata-kata kunci: hemodialisis, gagal ginjal kronik, gagal ginjal akut, indeks massa tubuh, tekanan darah